Impact of Advertisement on Children: Examining the Effects of Advertising on Children (Journal of Advances and Scholarly Researches in Allied Education, 2020)
A kind of communication that is paid for is advertising. It informs audiences about variousgoods, services, or concepts. This essay discusses commercials that were shown on television. Currently,television has a significant impact on our everyday lives. Children's exposure to advertisements has adiminishing effect with time. In reality, advertising raises children's knowledge of a variety of topics,including entertainment, culture, news, sports, and the newest inventions and fashion trends. Despite this,all of these advertising have a detrimental effect on kids' minds. This essay discusses its advantages anddisadvantages, as well as preventative measures and ways to mitigate them.